2020
DOI: 10.15252/msb.20209569
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the virulence gene interactome withCRISPR/dCas9 in the human malaria parasite

Abstract: Mutually exclusive expression of the var multigene family is key to immune evasion and pathogenesis in Plasmodium falciparum, but few factors have been shown to play a direct role. We adapted a CRISPR‐based proteomics approach to identify novel factors associated with var genes in their natural chromatin context. Catalytically inactive Cas9 (“dCas9”) was targeted to var gene regulatory elements, immunoprecipitated, and analyzed with mass spectrometry. Known and novel factors were enriched including structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
64
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 107 publications
14
64
2
Order By: Relevance
“…To begin to explore whether inhibition of ACS could affect these downstream pathways, we studied the localization of ACS using an endogenous GFP-tagged ACS parasite line (Fig S9a-b). ACS-GFP localized to the cytosol, although it was unclear whether it is also expressed in the nucleus in P. falciparum (Fig 3c), as previously observed in apicomplexan parasites (27,30,31). To verify this localization, we stained wild-type parasites with ACS immune serum.…”
Section: Coa-panam Targets Acssupporting
confidence: 53%
See 1 more Smart Citation
“…To begin to explore whether inhibition of ACS could affect these downstream pathways, we studied the localization of ACS using an endogenous GFP-tagged ACS parasite line (Fig S9a-b). ACS-GFP localized to the cytosol, although it was unclear whether it is also expressed in the nucleus in P. falciparum (Fig 3c), as previously observed in apicomplexan parasites (27,30,31). To verify this localization, we stained wild-type parasites with ACS immune serum.…”
Section: Coa-panam Targets Acssupporting
confidence: 53%
“…Here, we have conclusively demonstrated for the first time that CoA-PanAm is the active metabolite that inhibits ACS. With the previously suggested role of ACS in regulating the acetylome, transcriptome and metabolome (including fatty acid elongation) (27,28,30,31,39) and the corresponding cytoplasmic/perinuclear (this study) and nuclear localization of ACS for these functions (31), it could be hypothesized that these pathways are affected by CoA-PanAms.…”
Section: Discussionmentioning
confidence: 78%
“…However, although we have identified a panel of PfHMGB1-binding target genes at their upstream regions in P. falciparum , the transcriptional activities of these genes are not directly controlled by this factor. A recent study also shows that PfHMGB1 is not present in the protein complex binding to var gene loci ( 45 ). Therefore, differential expression of those genes in the Pfhmgb1 -KO line is a consequence of nuclear reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…A repressed state in contrast—extensively studied on the example of var genes—is maintained by heterochromatin protein HP1, histone deacetylase HDA2 and the histone lysine methyltransferase SET2 and marked by H3K9me3 rendering these genes heterochromatic [ 94 , 95 , 96 , 97 ]. Furthermore, a chromatin-remodeling enzyme [PF3D7_0624600] and sirtuin proteins influence chromatin condensation [ 98 , 99 ], and the incorporation of noncoding RNAs complement the var gene-switching mechanism by silencing the gene locus via its sense—activating via its antisense—lncRNA [ 90 , 100 ]. Sexual commitment is known to be regulated by the epigenetic cascade starting with Ap2-G expression being repressed by HP1, which is evicted upon gametocyte development 1 (GDV1) association to heterochromatin, and GDV1 itself is controlled by the gdv1 antisense RNA [ 35 , 97 , 101 , 102 ].…”
Section: Epigenetic Regulation Of Transcriptional Activitymentioning
confidence: 99%
“…In a pioneering study, Ji and Arnot identified and classified the first SWI2/SNF2 enzyme (Snf2L) with approximately 60% sequence homology to the ATPase domain of the yeast ISWI remodeler [ 127 ]. Since then, only a few studies addressed apicomplexan remodelers [ 98 , 128 ]. A genome-wide mutagenesis screen proposed one of the plasmodial remodelers to be essential and another two as putatively essential in asexual blood stages [ 9 ].…”
Section: Chromatin Remodeling Enzymesmentioning
confidence: 99%